HUBUNGAN KEMANDIRIAN DENGAN MINAT BERWIRAUSAHA ILUNI PRODI D3 JURUSAN KESEJAHTERAAN KELUARGA FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - Darmayanti, Regina; Elida, Elida; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2014)
The purpose of research is to analyze the relationship between autonomy with interest to entrepreneur of alumna study program D3 in the department of Home Economic Faculty of Engineering State University of Padang. This research is a descriptive correlational study. The population as many as 122 people alumna study program D3 Food & Beverage and Fashion finished 2008 until 2012 and be domiciled in West Sumatera. Sample election techniques in the study using purposive sampling technique as many as 43 people. Data collection techniques with a structured questionnaire based on Likert scale that has been tested for validity and reliability. Based on the survey results revealed the percentage of autonomy overall categorized as low (62%), interest to enterpreneur alumna study program D3 in the department of Home econimic overall categorized as low (58%). The results showed that there is a Positive and significant relationship between autonomy with interest to enterpreneur of alumna study program D3 in the department of Home Economic Faculty of Engineering State University of Padang.Keywords: Autonomy and Interest to Enterpreneur